Resistance training and hormone replacement increase MMP-2 activity, quality and quantity of bone in ovariectomized rats - Markus V.C Souza; Anderson D. S Lino; Leandro G. D Ruffoni; Mateus M. Domingos; Marina R. Barbosa; Maria F C. Rodrigues; Fabiano C. Ferreira; Luciane M. Tomaz; Gustavo H. R. Canevazzi; Natália S. Silva; Jeferson A. A. Teixeira; Richard D. Leite; et al. (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS The aim of the present study was to investigate the influence of resistance training (RT) and hormone replacement (HR) on MMP-2 activity, biomechanical and physical properties bone of ovariectomized (OVX) rats. METHODS Sprague-Dawley female rats were grouped into six experimental groups (n = 11 per group): sham-operated sedentary (SHAM Sed), ovariectomized sedentary (OVX Sed), sham-operated resistance training (SHAM RT), ovariectomized resistance training (OVX RT), ovariectomized sedentary hormone replacement (OVX Sed-HR), and ovariectomized resistance training hormone replacement (OVX RT-HR). HR groups received implanted silastic capsules with a 5% solution of 17β-estradiol (50 mg 17β-estradiol/ml of sunflower oil). In a 12-week RT period (27 sessions; 4-9 climbs) the animals climbed a 1.1 m vertical ladder with weights attached to their tails. Biomechanical and physical bone analyses were performed using a universal testing machine, and MMP-2 activity analysis was done by zymography. RESULTS Bone density and bone mineral content was higher in the RT and HR groups. The MMP-2 activity was higher in the RT and HR groups. The biomechanical analysis (stiffness, fracture load and maximum load) demonstrated better bone tissue quality in the RT associated with HR. CONCLUSION The RT alone as well as when it is associated with HR was efficient in increasing MMP-2 activity, biomechanical and biophysical properties bone of ovariectomized rats.